CHALLENGES OF TEACHING SUBJECT-AUXILIARY INVERSION - Nicholas Bwalya, Pethias Siame, Kennedy Njenje Kangwa; Djalilova Malika Shuxratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This study explores the phenomenon of auxiliary inversion in the English language and its corresponding challenges among learners and teachers at Nkulumashiba Secondary School in Luanshya, Zambia. The aim of the study is to improve English language education in Secondary schools and potentially serve as a basis for the development of instructional materials and interventions that can enhance learners’ overall syntactical competence. Using a qualitative approach, the study gathered and analyzed data through interviews and questionnaires. Primary data was collected using 28 respondents/informants who were selected purposively who included 3 teachers and 25 learners of English. The generative grammar theory was used to underpin the study. The study reveals that learners encounter difficulties with auxiliary inversion because the structural exponent is not adequately taught. The study further shows that there is a mismatch between the curriculum and the books in terms of the content. The further challenge is that the existing information about inversions is scanty hence both learners and teachers face critical challenges. Teachers also lack the required pedagogical approaches to teaching English inversion which eventually impedes the acquisition and masterly of knowledge and skills by the learners. The findings of this research have practical implications for English language teachers and curriculum developers. Therefore, eradicating the challenges encountered by learners regarding auxiliary inversion and delineating effective approaches would contribute to the ongoing efforts to improve English language education.